Urne rinviate per il CoViD-19: la soluzione di (inattesi) conflitti tra diritto al voto e diritto alla salute (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Once the CoViD-19 emergency broke out, the Italian government decided to delay the referendum on the constitutional reform about the number of MPs (scheduled for March 29) and, subsequently, also the regional and municipal elections, scheduled for May. This contribution considers the possible conflicts between right to health and right to vote and evaluates their solutions, also looking at the decisions made in other States about the opportunity to maintain the “rites of democracy” in times of health emergency.
Keywords: CoViD-19; pandemic emergency; delaying voting; right to vote; right to health